Pengembangan Aplikasi Pemetaan Desa untuk Kuliah Kerja Nyata dengan Geotagging berbasis Android (Studi Kasus : Mahasiswa Universitas Brawijaya) - Alif Andarta Al Falah; Agi Putra Kharisma; Komang Candra Brata (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2021)
Real Work Lecture (KKN) is an activity that cannot be separated from lecture activities and is a must for every student who attends a minimum of Bachelor's Degree (S.I) in higher education institutions. An important factor that can influence the success of KKN is the selection of villages for KKN. The villages available for KKN are located in community complexes with different development sectors, problems and environments. To help alleviate this problem, there is a platform that can help determine the location of KKN that is relevant to students. The StudyDesa application is based on Android and uses geotagging technology and camera sensors to help mapping KKN villages. This study uses the waterfall method, the method was chosen because the functional requirements that exist in the system have been defined clearly from the start and there are no changes. The tests of the StudyDesa application are functional, compatibility and usability testing. Functional testing is performed on all functionality and produces a value of 100%. Compatibility testing can run on all tested devices, namely the 3 most Android versions used by the Indonesian people in 2021. Usability testing produces a success rate of 94.28% while the System Usability Scale (SUS) produces an average value of 85.5 or if viewed on the conversion scale it is located in category B which means it is acceptable for students.